Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management

Whai Rawa, Whai Mana, Whai Oranga: Creating a world-leading indigenous blue economy - Mika, Jason; Rout, Matthew; Reid, John; Bodwitch, Hekia; Gillies, Annemarie; Hikuroa, Daniel; Mackey, Leane; Awatere, Shaun; Wiremu, Fiona; Rakena, Mylene; Davies, Kate; Robertson, Natalie (2019)
Keywords: environment; hapū politics; iwi politics; kaitiakitanga; mātauranga māori